Homalomena sungaikeliensis, a new species of Bornean aroids from Indonesia - Irsyam, A. S. D; Setiawan, A. A.; Hariri, M. R. (Rheedea, 2025)
Homalomena sungaikeliensis, a new species within the family Araceae, is described from West Kalimantan, Indonesian Borneo. This species exhibits morphological characteristics that distinguish it from other previously documented scintillating-velutinous Homalomena in Borneo. While exhibiting affinities with H. hottae, H. sungaikeliensis can be differentiated by the arrangement of pistillate flowers in three spirals, globose creamy-white staminodes, and staminate flowers comprising three to four white stamens. A detailed morphological diagnosis is presented, accompanied by data on its geographic distribution, phenology, and taxonomic distinctions to support accurate delimitation and identification.